Changes in physical activity among coronary and hypertensive patients: A longitudinal study using the Health Action Process Approach. Issue 3 (4th March 2017) - Steca, P.; Pancani, L.; Cesana, F.; Fattirolli, F.; Giannattasio, C.; Greco, A.; D'Addario, M.; Monzani, D.; Cappelletti, E.R.; Magrin, M.E.; Miglioretti, M.; Sarini, M.; et al.
Abstract : Objectives : Physical activity (PA) is a key factor in cardiovascular disease prevention. Through the Health Action Process Approach (HAPA), the present study investigated the process of change in PA in coronary patients (CPs) and hypertensive patients (HPs). Design : Longitudinal survey study with two follow-up assessments at 6 and 12 months on 188 CPs and 169 HPs. Main outcome measures : Intensity and frequency of PA. Results : A multi-sample analysis indicated the equivalence of almost all the HAPA social cognitive patterns for both patient populations. A latent growth curve model showed strong interrelations among intercepts and slopes of PA, planning and maintenance self-efficacy, but change in planning was not associated with change in PA. Moreover, increase in PA was associated with the value of planning and maintenance self-efficacy reached at the last follow-up Conclusions : These findings shed light on mechanisms often neglected by the HAPA literature, suggesting reciprocal relationships between PA and its predictors that could define a plausible virtuous circle within the HAPA volitional phase. Moreover, the HAPA social cognitive patterns are essentially identical for patients who had a coronary event (i.e. CPs) and individuals who are at high risk for a coronary event (i.e. HPs).